Remote ischemic perconditioning attenuates ischemia/reperfusion‐induced downregulation of AQP2 in rat kidney - Kristensen, Marie Louise V. (Physiol Rep, 2016)
Renal ischemia/reperfusion (I/R) can lead to impaired urine concentration ability and increased fractional excretion of sodium (FeNa). Local ischemic preconditioning improves renal water and sodium handling after I/R injury. Here, we investigate whether remote ischemic perconditioning (rIPeC) prevents dysregulation of renal water and salt handling in response to I/R injury and mechanisms that may be involved. Rats were subjected to right nephrectomy and randomized into a sham group or an I/R group. In the I/R group, rats were subjected to 37 min of renal ischemia and 3 days of reperfusion. rIPeC was applied to the abdominal aorta. Blood and urine were collected on day 3 postoperatively for clearance studies. The expression of aquaporins (AQPs) and the sodium transporter Na–K‐ATPase were analyzed using immunoblotting and immunohistochemistry. I/R injury resulted in polyuria, increased FeNa, and decreased urine osmolality compared to sham rats. rIPeC attenuated the increase in FeNa and the decrease in urine osmolality. Expression of AQP1, AQP2, phosphorylated AQP2 (pAQP2), and Na–K‐ATPase was downregulated in I/R rats. rIPeC attenuated the reductions in AQP2 and pAQP2 expression. Immunohistochemistry revealed decreased labeling of Na–K‐ATPase in the outer medulla in I/R kidneys compared to kidneys from sham and I/R + rIPeC rats. After renal ischemia, the expression of Na–K‐ATPase was substantially reduced in the outer medullary thick ascending limb. In conclusion, our data suggest that rIPeC might prevent dysregulation of renal water and salt handling via regulation of AQP2 expression and phosphorylation as well as via regulation of Na–K‐ATPase expression in I/R rat kidneys.